Effects of timing of induced luteolysis in embryo donor mares on reproductive performance and pregnancy rate in recipient mares - Goretti, R. G.; Araujo, R. R.; Rocha Filho, A. N. [UNESP]; Araujo, G. H. M. [UNESP]; Lopes, E. P.; Guimaraes, J. D. (Elsevier B.V., 2011)
The objective was to evaluate the effects of giving prostaglandin F(2 alpha) (PGF) to donor mares 48 h prior to embryo collection. Non-lactating donor mares (n = 20 estrous cycles in 10 mares), ranging from 2.5 to 10 y of age and 400 to 500 kg of body weight were used from September 2004 to February 2005 in the southern hemisphere (Brazil). Donor mares were randomly assigned in a cross-over design study. During a Treated cycle, 7.5 mg PGF was given 48 h prior to embryo collection, whereas in the Control cycle, 7.5 mg PGF was given at embryo collection. In Treated Cycles, serum progesterone concentrations decreased between the day of PGF treatment and the day of embryo collection (13.9 +/- 5.4 and 0.5 +/- 0.3 ng/mL, respectively; P < 0.05). In Treated versus Control cycles, the interovulatory interval was shorter (14.9 +/- 0.9 vs 17.5 +/- 1.1 d, P < 0.05). However, there was no significant difference between these groups for the interval from PGF to ovulation (average, 9.8 d), embryo recovery rate (average, 75%), embryo quality, uterine protein concentration, and pregnancy rate in recipient mares (average, 87% at 15 d after ovulation, with no pregnancy loss detected by 60 d). In conclusion, giving donor mares PGF 48 h prior to embryo collection reduced the average interovulatory interval by approximately 2.5 d, thereby potentially increasing the numbers of embryos that could be collected during a breeding season, with no deleterious effects on embryo recovery rate, embryo quality, or pregnancy rate in recipient mares. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Prostaglandin F(2 alpha); Interovulatory interval; Embryo recovery rate; Embryo quality; Uterine protein; Pregnancy rate